Participatory training scheme in area-based development strategy. - Occidental, Alicia P. (Discussion paper / Renewable Resource Economics and Management Research Program, 1989)
Summary of a Ph.D. Dissertation in Community Development... presented in the RREM seminar series... June 18, 1988 at the Agricultural Education Lecture Hall, DAERS, UP at Los Baños.